The challenges of transmitting family values in multi-cultural contexts - Hyjer Dyk, Patricia (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Across time and cultures, the institution of the family remains resilient. Although the family is but one component of a complex social system, it remains the setting in which a child’s first social development occurs. Yet the family is situated in a sociocultural environment with numerous socialization agents complementing and vying for influence as to the values that the next generation of citizens should adopt. This conceptual paper will articulate competing elements within the social system that contend for the socialization role. Ongoing scholarly inquiry will need to gauge the relative importance of these factors for supporting or challenging the parents’ transmittal of their family values to the next generation. To aid in this endeavour, a systems model provides a lens that can be employed by scholars to understand family processes in multi-cultural contexts and is useful in historical analyses of the transmission of family values.
Keywords: socialization; values; family; social system model